Hubungan Antara Kemampuan Membaca Pemahaman Dengan Kemampuan Memahami Soal Cerita Matematika Siswa Kelas V Sekolah Dasar - Alma Diliana; Heri Hadi Saputra; Heri Setiawan (Pendagogia: Jurnal Pendidikan Dasar, 2021)
This study aims to find out the relationship between the ability to read understanding and the ability to understand the math story of grade V students at SDN 3 Midang, West Lombok Regency. This research is quantitative research with correlation method. The population in this study was all grade V students at SDN 3 Midang, which numbered 35 students. Sampling techniques use saturated sampling techniques where all populations are sampled, the method used for data retrieval is in the form of tests. The data obtained is then processed by product moment correlation analysis techniques. The results showed that there is a positive relationship between the ability to read understanding and the ability to understand the math story of grade V students at SDN 3 Midang, Gunung Sari Subdistrict, West Lombok Regency, which is shown by the results of the data using product moment correlation where > at a significance level of 5% namely 0.79 > 0.334, so that Ha is accepted and Ho rejected. This shows that there is a relationship between the ability to read understanding and the ability to understand the problem of the student's math story